The Students’ Preference on Online Learning Platform for English Writing Skills - Aulia Andhini; Tasyakurna, Annisa; Raputri, Egi (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2024)
The technological development has influenced the educational aspect in supporting the teaching and learning process that can be run online. Online learning has been started commonly used for teaching English. This process is also facilitated by the existence of the online platforms. The teachers need to know the students’ preference towards the online platforms in order to achieve effective and efficient online learning. It has evolved into the indicator for evaluating the online learning for teaching English writing skills. Thus, the schools and the teachers can determine which online platforms are appropriate to use on the students. Thus, this research aimed to find out the students’ preference on online learning platforms for English writing skills in Senior High School 1 Bagan Sinembah. The criterions are language learning potential, meaning focus, learner fit, authenticity, positive impact and practicality. This is descriptive studies with detail analysis of students’ preference on online platforms like Zoom, E-learning, WhatsApp (WA) and Schoology. E-questionnaire was distributed to the students for collecting the data. E-learning obtained the highest percentage from natural science students with 74,0% and WhatsApp got the highest percentage from social science students with 68,3% as the suitable online platform for English writing skills for the students to learn and improve their writing skill when using the tools of those platforms. Therefore, it can be concluded that the students had different preferences in choosing the online platform for learning English writing skills. This preference leads us to believe that the online platforms can give the benefit of the students’ writing skill. It can be as the consideration for the teacher and decision-maker at school to choose the appropriate platform for students to be used.